Approaching the Unknown. The COVID-19 pandemic, political parties and digital adaptations: party élites' perceptions in Italy and Spain - Vittori, Davide; Barberà, Oscar (Frontiers in Political Science, 2023)
COVID-19 impacted the everyday life of European citizens, profoundly transforming long-standing habits between 2020 and 2022. During the first stages of the pandemic, the executives took the lead, but politics was not halted, parliaments were not closed, and parliamentary groups still continued working through digital means. Political parties and their élites were also active and also heavily relied on digital tools. So far, there has been very scarce research trying to understand how political parties and political elites coped with such swift digital move. This paper aims to fill this gap and contribute to understand what shaped the élites' perceptions of such digital adaptation's processes during the COVID-19 pandemic. In order to answer to these questions, we launched a pilot survey among party élites in Spain and Italy during the pandemic. Our results point out how parties quickly adapted to executive online meetings. However, the highest representative organs met online less frequently. As for the élites' adaptation, we find that socio-demographic characteristic of the élites matter, but only to a limited extent. The same goes for the future prospects in the use of digital tools within political parties.Approaching the Unknown. The 2020 COVID pandemic, political parties and digital adaptations: party élites' perceptions in Italy and Spain